ALIRAN SESAT DALAM PERSPEKTIF HUKUM PIDANA ISLAM DAN HUKUM PIDANA NASIONAL - Yulkarnain Harahab; Mr. Supriyadi (Fakultas Hukum Universitas Gadjah Mada, 2008)
The disseminator and participant of deviant’s sects can be accused as an “apostate” or “murtad”. They have committed “hudud crime” or “jarimah hudud” and can be punished by death sentence or subsidiary sanction. Nevertheless, the sanctions cannot be implemented because Indonesia is not Islamic state. There is no law enforcement towards the participant of deviant sects. But, they are only requested to be mass repented. The argumentation is that the participants of deviant’s sects are only a victim, so the process of law enforcement must be adjusted to the leader or disseminator of deviant sects.